2017 Pacific Standard Time: LA/LA - "The Latino Museum of History, Art and Culture (1995-2000) Revisited"
Photography by Oscar Castillo on display in Napa Hall at CSU Channel Islands for the 2017 Pacific Standard Time LA/LA: "The Latino Museum of History, Art and Culture (1995-2000) Revisited.